Trusting “Gangbangers” in war and peace - HALFF, Gregor (Institutional Knowledge at Singapore Management University, 2013)
The stage for this case is set in South Central LA, the infamous battleground of bloody gang wars, and the original breeding ground for rap and hip hop music. The narrative zooms in on the charismatic Alfred Lomas, who since leaving prison and his gang, has set up a business that requires him to maintain strong links to the warring factions, while at the same time ensuring that neither he nor his team gets caught up in the gangs again: His company LA Gang Tours takes visitors through the urban war zone, and the proceeds from the tours are used for community interventions. In a peacekeeping effort, former gang members de-escalate conflict between gangs, and break the chain of violence on the streets. The LA police are grudgingly supportive, but the business isn’t growing. Alfred ponders various growth strategies, as each will affect the network of trust that he has established with the gangs, the police and the tourists.